Mediation as a nothing to lose mode for alternative mode of dispute resolution in construction works - Kamarudin, Abdul Rani (LexisNexis, 2012)
This paper is on mediation, an effective and affordable complement to litigation. Mediation may be opted for in a wide range of subject matters, such as in civil and commercial disputes, matrimonial, personal injury, environmental and labour disputes, among others. It is a nothing to lose alternative dispute resolution, and why disputing parties should resort to it as their first option, and for them to determine for themselves how their disputes should be resolved particularly so for disputes in construction projects where disagreements must be resolved as quickly as possible to meet the project time line.